Global Research on Augmented Reality in Education: Bibliometrics Analysis - Ramadhani, Indri Anugrah; Asrul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This research aims to analyze bibliometrics related to Augmented Reality (AR) in the field of education which focuses on the number of citations, classification based on aspects (field, journal, researcher), the relationship between augmented reality topics and other topics, and the relationship between authors who research on the topic augmented reality. The method used in this research uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. The research results show that the number of citations on the topic of Augmented Reality is 48,823. Quality Education is ranked first based on the field of (SDGs) with a total of 2461 articles and the journal AIP Conference Proceedings is the journal that publishes the most articles on the topic of augmented reality. The results of visualization analysis using Vosviewer, produce the latest research topic trends such as augmented reality being linked to medical education, and some topics have not been widely researched such as augmented reality being linked to preschool children.